Effects of inorganic copper injection in beef cows at late gestation on fetal and postnatal growth, hematology and immune function of their progeny - Rodriguez, Alejandro Martin; Lopez Valiente, Sebastian; Mattioli, Guillermo Alberto; Maresca, Sebastian (Elsevier, 2021)
To determine if Cu injection during late gestation can affect fetal and postnatal growth, hematology and immune function of progeny, 70 multiparous pregnant Angus cows, at 219 ± 15 d of gestation, were ranked by BW and BCS and randomly assigned to one of two treatments: Cu + (n = 35) in total 160 mg of Cu were administered subcutaneously in two moments (80 mg per moment) at 64 ± 15 d and 54 ± 15 d prepartum; and Cu- (n = 35), in total of 16 ml of sterile NaCl solution (9 g / l) were administered subcutaneously in two moments (8 ml per moment) at 64 ± 15 d and 54 ± 15 d prepartum. Calves from both treatments were weaned at 260 ± 15 d of age, male calves were separated from female calves and stockered on natural pastures until 690 ± 15 d of age, then placed into a feedlot for 104 d before slaughter. At the beginning of the experiment, cows Cu serum concentration was similar (P = 0.34) between treatments and these reflected a severe Cu deficiency (Cu + = 24.2 ± 1.5 μg/dl; Cu- = 22.2 ± 1.4 μg/dl). At calving, Cu serum concentration was greater (P < 0.01) in Cu + cows than Cu- cows. Copper serum concentration in calves from Cu + cows was greater at birth (P = 0.02) and 75 ± 15 d of age (P < 0.01) and tended (P = 0.07) to be greater at 160 ± 15 d of age compared to calves from Cu- cows. Calf BW at birth did not differ (P > 0.10) between treatments, however, calf BW adjusted at 75 d of age tended to be greater (P = 0.10) in calves from Cu + cows compared to calves from Cu- cows. Calf ADG from birth to 75 d of age was greater (P = 0.04) in calves from Cu + cows compared to calves from Cu- cows. Calf hematological parameters and titers of neutralizing antibodies against BHV-1 after primary and secondary vaccination against respiratory diseases did not differ (P > 0.10) between treatments. During finishing period, steers BW, 12th rib fat thickness and LM area were not affected (P > 0.10) by treatments. In summary, inorganic Cu injection during late gestation in Cu deficient beef cows allows to increase Cu serum concentration in calves from birth to 160 d of age. This event was associated with an increase in ADG and a tendency to increase BW during the first 75 days of life. After 75 days of age, any effect on the offspring performance was not observed.